2019
DOI: 10.1111/ejn.14648
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine modulates the optomotor response to unreliable visual stimuli in Drosophila melanogaster

Abstract: State‐dependent modulation of sensory systems has been studied in many organisms and is possibly mediated through neuromodulators such as monoamine neurotransmitters. Among these, dopamine is involved in many aspects of animal behaviour, including movement control, attention, motivation and cognition. However, the precise neural mechanism underlying dopaminergic modulation of behaviour induced by sensory stimuli remains poorly understood. Here, we used Drosophila melanogaster to show that dopamine can modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Previous experimental work has implicated FB circuits in a variety of behaviors that require directed movements, including operant visual learning ( Liu et al, 2006 ), obstacle avoidance ( Harley and Ritzmann, 2010 ), nociceptive avoidance ( Hu et al, 2018 ), and head optomotor responses ( Akiba et al, 2020 ). Further, recent physiological recordings have demonstrated that PB-FB columnar neurons convey the head direction representation from the left and right PB to the FB ( Shiozaki et al, 2020 ), and that, similar to the PEN neurons, PFN activity is likely modulated by self-motion inputs received in the NO ( Currier et al, 2020 ; Lu et al, 2020b ; Lyu et al, 2020 ; Shiozaki et al, 2020 ; Stone et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental work has implicated FB circuits in a variety of behaviors that require directed movements, including operant visual learning ( Liu et al, 2006 ), obstacle avoidance ( Harley and Ritzmann, 2010 ), nociceptive avoidance ( Hu et al, 2018 ), and head optomotor responses ( Akiba et al, 2020 ). Further, recent physiological recordings have demonstrated that PB-FB columnar neurons convey the head direction representation from the left and right PB to the FB ( Shiozaki et al, 2020 ), and that, similar to the PEN neurons, PFN activity is likely modulated by self-motion inputs received in the NO ( Currier et al, 2020 ; Lu et al, 2020b ; Lyu et al, 2020 ; Shiozaki et al, 2020 ; Stone et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental work has implicated FB circuits in a variety of behaviors that require directed movements, including operant visual learning (Liu et al, 2006), obstacle avoidance (Harley and Ritzmann, 2010), nociceptive avoidance (Hu et al, 2018), and head optomotor responses (Akiba et al, 2020). Further, recent physiological recordings have demonstrated that PB-FB columnar neurons convey the head direction representation from the left and right PB to the FB (Shiozaki et al, 2020), and that, similar to the PEN neurons, PFN activity is likely modulated by self-motion inputs received in the NO (Currier et al, 2020;Lu et al, 2020a;Lyu et al, 2020;Shiozaki et al, 2020;Stone et al, 2017).…”
Section: The Fb: a Structured Recurrent Network For Context-dependent Navigation And Sleepmentioning
confidence: 99%
“…Based on the morphological similarities, we assumed that one of the candidates of the post-synaptic neurons of P-FN neurons is FB interneurons, also known as pontine neurons 17,18 . Among the Gal4 drivers, NP2320-Gal4 is a driver that is reported in the previous papers to show clear labeling in pontine neurons 1922 . Figure 1b shows the morphological patterns of pontine neurons labeled with NP2320-Gal4 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…According to previous reports, pontine neurons regulate optomotor behavior and express tachykinin, a neuropeptide that regulates aggression 20,22,32 . Additionally, T1 dopamine neurons, which are upstream of pontine neurons, regulate aggression as well 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation